Toughness analysis of jute laminate composites as wrapping for cylindrical concrete columns - Achmad Jusuf Zulfikar; Yuhazri M.Y.; Siswo Pranoto; Din Aswan A. Ritonga; Zakir Husin (Teknik Mesin - Universitas Muhammadiyah Cileungsi, 2025)
This study investigates the potential of laminated jute composites (LJC) as a sustainable reinforcement material for cylindrical concrete columns (CCCs) by analyzing the effects of varying the number of LJC layers on mechanical performance. Concrete, widely used in construction, is limited by its low tensile strength, prompting the need for effective reinforcement methods. While previous research has explored natural and hybrid fiber composites, the specific role of jute laminates in enhancing toughness energy (MTE) and split tensile strength (STS) remains underexplored. Specimens were prepared according to ASTM C496, with up to four LJC layers applied using a vacuum bagging method. Experimental results revealed a significant increase in MTE and STS with additional LJC layers. The four-layer configuration (J4) achieved the highest performance, with an MTE enhancement of 17,800% and an STS improvement of over 300% compared to the control specimen. These findings highlight the synergistic relationship between tensile strength and energy absorption in LJC-reinforced CCCs. The study also identified an optimal layer configuration, emphasizing the need for further exploration of durability and long-term performance. This research establishes LJC as a cost-effective and environmentally friendly material for enhancing the mechanical properties of concrete structures, offering valuable insights into sustainable construction practices.